2022
DOI: 10.1155/2022/2561673
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Regulatory Factor Family Genes: At the Crossroads between Immunity and Head and Neck Squamous Carcinoma

Abstract: Objective. This study is aimed at investigating the regulating mechanisms of the interferon regulatory factor (IRF) family genes in head and neck squamous cell carcinoma. Methods. Based on the HNSC data in the ‘The Cancer Genome Atlas (TCGA)’ database, the expression pattern of IRF family genes was investigated. The association of IRFs family genes and survival outcomes were analyzed by Kaplan–Meier plotter web portal. The relation of IRF genes and tumor stages was evaluated by using stage plots and based on G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
(39 reference statements)
2
5
0
Order By: Relevance
“…In the field of OSCC, IRF4 were highly expressed in OSCC tumor samples compared to control samples and involved in tumor immunity-related signaling pathways. IRF4 indicated significant prognostic values and could be potential therapeutic biomarkers in targeting tumor immunity of OSCC 51 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the field of OSCC, IRF4 were highly expressed in OSCC tumor samples compared to control samples and involved in tumor immunity-related signaling pathways. IRF4 indicated significant prognostic values and could be potential therapeutic biomarkers in targeting tumor immunity of OSCC 51 .…”
Section: Discussionmentioning
confidence: 99%
“…
the oncogenic transcriptional program in malignant lymphoid cells 15 . However, research on the role of IRF4 in OSCC is still lacking 16 .In this study, we conducted a comprehensive bioinformatics analysis including functional enrichment analysis, CNV and immune infiltration analysis through Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases to identify key genes and explore the underlying molecular mechanisms involved in OSF into OSCC. We finally found the role of IRF4 in predictabilities of the transformation from OSF to the presence of OSCC.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Through bioinformatics analysis, we found that FSCN1 could interact with IRF4, which is involved in the oncogenesis of multiple cancers. For instance, IRF4 upregulation was correlated with survival outcomes in head and neck squamous carcinoma [ 33 ]. In cholangiocarcinoma, IRF4 promotes cancer proliferation as well as metastasis by regulating PI3K/AKT signaling [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through bioinformatics analysis, we found that FSCN1 could interact with IRF4, which is involved in multiple cancer oncogenesis. For instance, IRF4 upregulation was correlated with the survival outcomes in head and neck squamous carcinoma (33). In cholangiocarcinoma, IRF4 promotes cancer proliferation as well as metastasis via regulating the PI3K/AKT signaling (34).…”
Section: Discussionmentioning
confidence: 99%